The evil men do - McMahon, John, 1970- (McMahon, John, 1970- Detective P.T. Marsh, 2020)
"The author of The Good Detective delivers a gripping and atmospheric new novel in which a cop takes on a harrowing new case and confronts old personal demons. What if the one good thing you did in your life doomed you to die?"--